A Preliminary Study of the Effects of Venous Drainage Position on Arterial Blood Supply and Venous Return within the Conjoined Flap. Issue 2 (February 2019) - Xi, Shanshan; Cheng, Sheng; Lou, Junsheng; Qiu, Lingfeng; Yang, Qingwen; Yu, Wanping; Mei, Jin; Tang, Maolin
Abstract : Background: Conjoined flap viability is associated with arterial blood supply and venous return. This study aimed to assess the effects of venous drainage position on arterial blood supply and venous return within the conjoined flap. Methods: Fifty-four rats were divided randomly into three groups ( n = 18 per group). In experimental group 2, only the right intercostal posterior artery and the left iliolumbar vein were maintained; meanwhile, only the right intercostal posterior artery and the left intercostal posterior vein were preserved in experimental group 1. The control group had only the right intercostal posterior artery and vein preserved. The distances between angiosomes were measured. At 7 days after surgery, flap survival was evaluated, lead oxide–gelatin flap angiography was performed, and average microvessel density was assessed by hematoxylin and eosin staining, and lactate levels were assessed. Results: The distance between angiosomes I and II was the shortest, whereas angiosomes I and III were most distant ( p < 0.05). At 7 days after surgery, survival rates in experimental group 2 and experimental group 1 were both 100 percent, whereas 86.5 ± 1.6 percent of controls survived. Furthermore, angiogenesis was more obvious in experimental group 2 than in experimental group 1 and controls. Moreover, lactate levels were lower in experimental group 2 (7.47 ± 0.17 mM) and experimental group 1 (8.03 ± 0.31 mM) compared with control values (9.98 ± 0.37 mM; p < 0.05). Conclusion: Changes in position of venous drainage might cause continuous arterial high-pressure perfusion and venous superdrainage, which improves flap survival.